The speech ability on maxillary denture wearer: a systematic review - Meriyam Muchtar; Ike D. Habar (Journal of Dentomaxillofacial Science, 2018)
Objective: Getting information about on influence of denture bases design on speech ability on maxillary denture wearer.Methode: Electronic search in PubMed and Wiley online library databases to find articles that were published in last 20 years; between January 1998 to December 2017 with keywords â€œdenture basesâ€ and â€œspeechâ€. The articles were then selected by reviewing the title and abstract.Result: The initial search obtained 52 articles. Then selected by involving the inclusion criteria. Finally, it gain 2 articles only that suitable with the inclusion criteria.Conclusion: Speech ability is usually not the main complain of denture wearer. Subjects with inappropriate design of the prosthetic base, disposition of artiï¬cial teeth and functional quality (retention, support, stability) have dyslalia when pronunciation of separate phonemes is changed.